Presse et corps policiers : complicité et conflit - Parent, Georges-André (Criminologie, 1987)
The literature abounds with studies showing the cultural gap and the hostility that exists between journalists and the police. During the 19th century in the United States, however, a complicity eminently profitable for both was rapidly established between constables and reporters for the first penny newspapers. The confrontations and mass rallies of the 60' s saw the role of journalists change to become no longer the servile and docile distributors of a particular image of crime, the criminal and police work. Journalists suddenly found themselves on the side of the “criminals”, facing the truncheons of militant police. In Montreal, a public relations service was subsequently created to restore the positive image of the police and try to reestablish the control of information. Since the newspapers were more commercial than intellectual enterprises, complicity, both official and unofficial, was quickly reestablished, giving rise to a rather doubtful relationship between journalists and the police. It was about ten years after the October crisis, when the majority of journalists identified more with the protesters than with the repressive forces, that the Quebec Police decided to restore media/police relationships to their former state. A communications service was created, which, in little more than ten years, enabled the police authorities to exercise an almost total control over information; only what served the strategy of the police was to be published. For the R.C.M.P., the honeymoon came to an end with the creation of the Keable and McDonald Commissions. In 1977, there were five policemen attached to the public relations service of the R.C.M.P. in Montreal. In 1986, a single officer remains and no longer even bears the title of official communications or public relations officer. Everywhere in Quebec, journalists seem to have traded their ability to inform for their daily ration of diverse facts, and it is still the disturbing image of crime and criminals that they blithely publish, making the media true instruments of social control.